Respiratory mortality of childhood, adolescent and young adult cancer survivors. Issue 10 (10th May 2018) - Fidler, Miranda M; Reulen, Raoul C; Bright, Chloe J; Henson, Katherine E; Kelly, Julie S; Jenney, Meriel; Ng, Antony; Whelan, Jeremy; Winter, David L; Frobisher, Clare; Hawkins, Michael M
Abstract : Background: Exposure to radiation and/or chemotherapy during cancer treatment can compromise respiratory function. We investigated the risk of long-term respiratory mortality among 5-year cancer survivors diagnosed before age 40 years using the British Childhood Cancer Survivor Study (BCCSS) and Teenage and Young Adult Cancer Survivor Study (TYACSS). Methods: The BCCSS comprises 34 489 cancer survivors diagnosed before 15 years from 1940 to 2006 in Great Britain. The TYACSS includes 200 945 cancer survivors diagnosed between 15 years and 39 years from 1971 to 2006 in England and Wales. Standardised mortality ratios and absolute excess risks were used. Findings: Overall, 164 and 1079 respiratory deaths were observed in the BCCSS and TYACSS cohorts respectively, which was 6.8 (95% CI 5.8 to 7.9) and 1.7 (95% CI 1.6 to 1.8) times that expected, but the risks varied substantially by type of respiratory death. Greatest excess numbers of deaths were experienced after central nervous system (CNS) tumours in the BCCSS and after lung cancer, leukaemia, head and neck cancer and CNS tumours in the TYACSS. The excess number of respiratory deaths increased with increasing attained age, with seven (95% CI 2.4 to 11.3) excess deaths observed among those aged 50+ years in the BCCSS and three (95% CI 1.4 to 4.2) excess deaths observed among those aged 60+ years in the TYACSS. It was reassuring to see a decline in the excess number of respiratory deaths among those diagnosed more recently in both cohorts. Conclusions: Prior to this study, there was almost nothing known about the risks of respiratory death after cancer diagnosed in young adulthood, and this study addresses this gap. These new findings will be useful for both survivors and those involved in their clinical management and follow-up.